PELATIHAN PEMBELAJARAN DARING DITENGAH PANDEMI COVID-19 DENGAN MENGGUNAKAN APLIKASI ZOOM METTING DAN GOOGLE CLASSROM - Lukman Hakim Siregar; Nurtiani Simamora; Doni Damara Putra; Mara Ganti Nasution (Institut Pendidikan Tapanuli Selatan, 2022)
The Covid-19 pandemic not only has an impact on the community's economy but has almost changed the entire order of social life, especially in the world of education. Based on central and local government policies that require online learning, of course, creates a dilemma for teachers amid limited IT knowledge, especially those in remote villages. The selection of the right method in the teaching and learning process is a serious problem, several factors need to be considered, such as the readiness of schools, teachers and students in the implementation of the online learning process. Of course, the application used must be accessible and understood by every teacher and student so that learning objectives are still achieved. The purpose of this community service activity is to implement the Tri Dharma of Higher Education, especially Community Service by equipping teachers with expertise or skills in the IT field, especially online learning applications that can be used in the online teaching and learning process. The method used in this service activity is through a lecture system, explaining materials related to online learning applications based on Google Classroom, zoom meetings and direct practice of using the application with the help of a practice companion team for MtsS Hajijah Amalia Sari students located in Link. III Batunadua Julu ( Ex Siparau ), Kec. Padangsidimpuan Batunadua, Padang Sidimpuan City, North Sumatra, 22733.. The result of community service activities is that teachers can understand and be able to apply online learning methods such as google classroom so that the learning process can run effectively in the midst of the Covid 19 pandemic.